Bridging the research-practice gap in child and adolescent psychotherapy : a survey of New Zealand practitioners : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Psychology at Massey University - Kibblewhite, Joanna Joy (Massey University, 2002)
The conditions and characteristics of child and adolescent psychotherapy in clinical practice are known to differ from those found in research settings. This is a concern for psychologists who aim to provide evidence-based practice within the scientist-practitioner model. In partial replication of a previous North American survey (Kazdin, Siegel & Bass, 1990), this study drew on New Zealand mental health practitioners' experience in order to identify clinically relevant future research directions. Two hundred and three mental health practitioners from a variety of professional backgrounds reported on their assessment and treatment practices, perception of typical outcomes, beliefs about factors affecting outcome, and adherence to aspects of the scientist-practitioner model. Apart from the types of therapies used, the conditions and characteristics of practice reported here differed from those typically found in research. A number of research imperatives were identified including issues related to: developing clinically representative outcome studies; transporting empirically supported therapies to the clinic setting; and continuing the search for common factors to guide practice. The need to continually review and critique the research underlying empirical support for therapies was highlighted, as were the possible pitfalls of failing to do so.
Keywords: Child psychotherapy; Adolescent psychotherapy